Pengaruh Literasi Finansial Terhadap Perilaku Pengelolaan Keuangan Siswa Kelas XI SMA Global Islamic Boarding School - Miftahussalam, Miftahussalam; Ratumbuysang, Monry Fraick Nicky Gillian; Rahmattullah, Muhammad; Rizky, H. Maulana (Universitas Negeri Surabaya, 2024)
This research aims to 1) analyze the level of financial literacy of class XI students at SMA Global Islamic Boarding School and 2) analyze the influence of student financial literacy on financial management behavior in class The type of research used is a quantitative descriptive approach. The subjects in this research were class XI students at SMA Gobal Islamic Boarding School. The sample used was 77 respondents selected using the saturated sampling technique method. Data analysis used in this research uses simple linear regression analysis. The results of the research show 1) the financial literacy level of students at XI SMA Global Islamic Boarding School is at the Sufficent Literate level. where at this level they are grouped based on individuals who have knowledge and confidence in financial institutions and products and services including features, benefits and risks, rights and obligations, but there are still no skills in using financial products and services and 2) financial literacy has a significant effect on the financial management behavior of class XI students at Global Islamic Boarding School.